An evaluation of physical activity training in Australian medical school curricula. Issue 6 (June 2017) - Strong, Abigail; Stoutenberg, Mark; Hobson-Powell, Anita; Hargreaves, Mark; Beeler, Halle; Stamatakis, Emmanuel
Abstract: Objectives: To evaluate the current level of physical activity (PA) training provided to Australian medical students. Design: Individual interviews were completed via phone interview or online survey from June–October 2015. Methods: Program leaders from Australian medical schools, who were knowledgeable about their curriculum content, were invited to participate in the study. The number of programs, hours of PA training instruction, institutional attitude towards offering PA, barriers experienced, and content areas in which PA training was offered, were explored. Results: Seventeen of the 19 (89%) Australian medical schools participated in the study. Among the responding schools, 15 (88.2%) reported providing specific PA training to medical students. Thirteen of these 15 schools (86.7%) taught the national aerobic guidelines while only seven (46.7%) taught the national strength training recommendations. Four, five, and six year programs reported providing an average of 6.6, 5.0, and 12.3 h of PA training, respectively, across their entire curriculum. Only 42.9% of the schools that had PA training reported that it was sufficient for their medical students. Nearly half (41.2%) of the respondents reported no barriers to implementing PA training into their medical curricula. Conclusions: Most Australian medical schools reported including some PA training in their medical curriculum. Key topics, such as the national strength recommendations, however, were not taught by most schools. Given the importance of PA for the prevention and treatment of numerous mental and physical health outcomes, it is unlikely that the attention it currently receives adequately prepares medical students to treat patients.